2021
DOI: 10.3390/land10111220
|View full text |Cite
|
Sign up to set email alerts
|

History, Current Situation and Challenges of Gold Mining in Ecuador’s Litoral Region

Abstract: Gold mining in Ecuador has been present in the country since Inca times; over the years interest in the mineral has increased, leading to the creation of legislation to control the mining sector in a safe manner. The Litoral region consists of seven provinces, six of which have registered gold concessions; the most affected provinces are El Oro and Esmeraldas. The objective of this study was to analyze the historical and current situation of artisanal and industrial gold mining in the Litoral region of Ecuador… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Artisanal and large-scale gold mining can negatively affect the environment (health risks, change land use, and livelihood options) and cause serious impacts for miners and surrounding communities, causing conflicts over land ownership and use [19,20]. Despite all this, the miner takes the risks and works with the well-being and daily needs of his family in mind [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Artisanal and large-scale gold mining can negatively affect the environment (health risks, change land use, and livelihood options) and cause serious impacts for miners and surrounding communities, causing conflicts over land ownership and use [19,20]. Despite all this, the miner takes the risks and works with the well-being and daily needs of his family in mind [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…For the present study, samples came from Esmeraldas, located in Ecuador’s coastal zone. In this province, illegal, artisanal, and small-scale mining is carried out, where Hg is widely used for gold amalgamation, and impacts on the rivers in the north of the province due contamination by gold mining have been reported [68] , [74] . Hg water pollution is also attributed to current systems that can move metals from industrialized countries such as Japan and China towards the central Pacific [4] .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, concerning the environmental aspect, the Evaluation of Ecuador's Mining Policy Framework [57] notes that, in terms of environmental management, the country lacks technical regulations, adequate control, and awareness of the environmental impacts of mining, specifically for proper management of (i) large volumes of solid and liquid waste, (ii) biodiversity in the exploration phase, (iii) water resources, and (iv) emergency preparedness programs and their socialization with communities and authorities. In addition to the above, inhabitants located in mining areas reported that there is a lack of continuous control and monitoring by environmental authorities to verify their activities, call attention to them, and prevent future incidents before they are already unavoidable; for example, the collapse of a tailings dam in Ponce Enriquez that resulted in the contamination of the Tenguel River [58].…”
Section: Challenges Of Gold Mining In the Ecuadorian Andean Zonementioning
confidence: 99%